Strategic Assessment of the Efficiency of Diversification of the Industry Investment Portfolio - D. N. Gavrilina; A. S. Ogareva (Управленческое консультирование, 2021)
One of the effective special tools used to achieve the least risk and sustainable income of investment in enterprises is the investment portfolio. At the same time, one of the simplest and most effective strategies to minimize investor risk is its diversification.The article presents the results of the performed strategic financial analysis of the effectiveness of diversification of the formed sectoral investment portfolio using the example of large enterprises of the metallurgical industry. The choice of industry was determined by the fact that metallurgy is one of the fastest growing industries in the world economy.The article analyzes the strategic development trends of the metallurgical industry and considers the three largest companies in this industry (“MMK”, “Severstal”, “NLMK”). Their activity was analyzed in dynamics based on financial reporting data presented on company websites.Comparative analysis was carried out on such indicators of financial analysis as current liquidity ratios, equity and financial leverage concentration ratios, as well as interest-to-payment ratios, turnover of reserves and funds in turnover, profitability of the companies under consideration.In the resulting formation of the investment portfolio, correlation coefficients between the returns of the shares of these companies were calculated. It was established that the financial situation, as well as the low correlation coefficient between the assets of the reviewed companies, allow us to form from their shares an industry investment portfolio that minimizes the risks of a potential investor.